2018
DOI: 10.1017/s2045796018000203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mental illness on care for somatic comorbidities in France: a nation-wide hospital-based observational study

Abstract: Inadequate primary care of mentally ill patients leads to more serious conditions upon admission to hospital and avoidable hospitalisations. It is, therefore, necessary to improve primary care and prevention for those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
1
20
0
1
Order By: Relevance
“…Characteristics of the 23 included studies are presented in Table 1. Fourteen studies reported health care at end of life (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and 13 studies reported place of death in patients with a serious mental illness (13,28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and. Four studies reported both outcomes (28,(34)(35)(36).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the 23 included studies are presented in Table 1. Fourteen studies reported health care at end of life (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and 13 studies reported place of death in patients with a serious mental illness (13,28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and. Four studies reported both outcomes (28,(34)(35)(36).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There was great variability in the size of the study sample from which the sample of people with serious mental illness. In two studies (28,32), the whole sample comprised eligible adult subjects with serious mental illness, whom were included in the synthesis of results, whilst other studies presented results for subsamples with serious mental illness from a Most studies were from the USA (13,24,(30)(31)(32)34,35,38) and Canada (29,36,43); the remaining studies were from Denmark (41,42), the UK (28,44), France (39), the Netherlands (25), Australia (27,33), New Zealand (23), Japan (40) and Taiwan (26,37). The mean/median age of subjects ranged between 47 and 79.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations